No association of KIR3DL1 or KIR3DS1 or their alleles with ankylosing spondylitis. - McCappin, J; Harvey, D; Wordsworth, B; Middleton, D (2010)
We determined the alleles of KIR3DL1 and KIR3DS1 in a cohort of British Caucasian ankylosing spondylitis (AS) patients and HLA-B27-positive controls. We found no association in frequencies of the alleles of these genes in AS. In addition, no differences were found when the patients and controls were differentiated by gender.